Simvastatin Inhibits Endometrial Cancer Malignant Behaviors by Suppressing RAS/Mitogen-Activated Protein Kinase (MAPK) Pathway-Mediated Reactive Oxygen Species (ROS) and Ferroptosis. (14th October 2022) - Zhou, Dan; Wu, Qiuhua; Qiu, Huajuan; Li, Mi; Ji, Yanqin
Abstract : This paper was designed to explore the function of simvastatin as a chemotherapeutic drug on the endometrial cancer (EC) cell proliferation, invasion, and ferroptosis. Firstly, a number of in vitro experiments were conducted to determine the impact of different treatments of simvastatin on the Ishikawa cell invasion, proliferation, and colony formation. The concentration of DCFH-DA-labeled reactive oxygen species (ROS) in cells was assessed by flow cytometry. Enzyme-linked immunosorbent assay (ELISA) was performed to examine the intracellular contents of Fe 2+, malondialdehyde (MDA), and glutathione (GSH). Additionally, Western blot was utilized to measure the expression level of RAS/mitogen-activated protein kinase (MAPK)-related proteins and ferroptosis-related proteins in cells. The results showed that simvastatin at 10 μ M and 15 μ M apparently suppressed the proliferation of Ishikawa cells, colony formation, and invasion ability of Ishikawa cells, and upregulated the level of MDA and ROS, but downregulated the level of GSH. Besides, 10 μ M and 15 μ M of simvastatin promoted cell ferroptosis (up-regulation of Fe 2+ and TRF 1 protein level; down-regulation of SLC7A11 and FPN protein level) and lowered the RAS, p-MEK, and ERK protein level. Furthermore, experiments also revealed that the inhibitory effects of simvastatin on Ishikawa cell proliferation, colony formation, and invasion, as well as the promoting effects on oxidation and ferroptosis were reversed. All in all, simvastatin reduces the RAS/MAPK signaling pathway to inhibit Ishikawa cell proliferation, colony formation, and invasion, and promote cell oxidation and ferroptosis. This paper demonstrates the potential of simvastatin as a new anticancer drug for EC.